2018
DOI: 10.1159/000494799
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological and Neurophysiological Mechanisms Underlying Nicotine Seeking and Smoking Relapse

Abstract: Tobacco-related morbidity and mortality continue to be a significant public health concern. Unfortunately, current FDA-approved smoking cessation pharmacotherapies have limited efficacy and are associated with high rates of relapse. Therefore, a better understanding of the neurobiological and neurophysiological mechanisms that promote smoking relapse is needed to develop novel smoking cessation medications. Here, we review preclinical studies focused on identifying the neurotransmitter and neuromodulator syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 267 publications
(348 reference statements)
0
16
0
1
Order By: Relevance
“…This study aimed to examine whether and to what extent sex would affect the associations between initial e-cigarette use and subsequent cigarette smoking among American adolescents (aged [12][13][14][15][16][17]. Although the longitudinal associations between e-cigarette use and subsequent cigarette smoking had been documented [8][9][10], no previous studies examined the potential difference in this relationship by sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aimed to examine whether and to what extent sex would affect the associations between initial e-cigarette use and subsequent cigarette smoking among American adolescents (aged [12][13][14][15][16][17]. Although the longitudinal associations between e-cigarette use and subsequent cigarette smoking had been documented [8][9][10], no previous studies examined the potential difference in this relationship by sex.…”
Section: Discussionmentioning
confidence: 99%
“…Sex is a significant dimension for nearly all public health areas [ 13 ], and tobacco use is no exception. Evidence from laboratory experiments with non-human subjects indicated that the neurobiological mechanisms underlying nicotine seeking and metabolism differ between males and females [ 14 , 15 ]. Due to the presence of higher level of estrogen, females metabolize nicotine faster and experience lower rewarding effects of nicotine than males [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, low yield “light” cigarettes and “ultra-light” cigarettes have been designed by different tobacco processing companies, and they are suggested to contain fewer toxins compared to the normal “heavy” cigarettes (Popova et al 2018 ). Elsewhere, a study on nicotine reduction and its associated impacts has pointed out two required lines of action; preventing addiction and reduction or stoppage of tobacco consumption altogether, which never has an easy strategy towards tobacco cessation (Schmidt et al 2018 ). Whereas the use of e-cigarettes and light cigarettes as alternative ways to reduce tobacco toxins may be a successful strategy, controlling thousands of other tobacco toxins released during tobacco burning cannot be achieved by these techniques, which are focused only in lowering nicotine concentration levels in a cigarette (Auer et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The neurobiological underpinnings of nicotine dependence are complex, and several neurotransmitters, receptors, and pathways are implicated. 2 , 8 , 44 Chronic exposure to nicotine is associated with structural and functional neuroadaptations that drive dependence and promote continued use, 45 as well as pharmacogenetics, and untreated mental health disorders. The age at which someone starts smoking affects the extent of change, with people who started smoking in their teenage or young adult years being the most severely affected.…”
Section: Neurobiologymentioning
confidence: 99%